1980
DOI: 10.1524/ract.1980.27.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Recoil F- and Cl-Atoms with Liquid Aromatic Compounds and Additives

Abstract: Hot atom chemistry I Recoii labeling / "F / " "a j Aromatic substitution / Scavengers AbstractThe effect of additives such as elemental halogens, alkyliodides, satuiated and unsatuxated hydrocarbons, aniline, and diphenylpicrylhydrazil (DPPH) on the product yields for the reactions of "F, """CI, and "C1 recoii atoms with C.HSF and QH^CL was investigated. The behaviour of these additives as scavengers for thermal processes are compared with self-scavenging properties of aromatic Compounds towards halogen atoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1981
1981
1995
1995

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
(35 reference statements)
0
8
0
Order By: Relevance
“…C1 has generally been used for these studies, because it can be produced easily in a nuclear reactor. Also some work has been done with recoil atoms [5,12,13]. The best investigated aromatic Compounds are the liquid chlorobenzenes and in particular CeHsCl: the chlorine atoms in the molecules serve as the source of ^^""Cl and C1 atoms.…”
Section: Introductionmentioning
confidence: 99%
“…C1 has generally been used for these studies, because it can be produced easily in a nuclear reactor. Also some work has been done with recoil atoms [5,12,13]. The best investigated aromatic Compounds are the liquid chlorobenzenes and in particular CeHsCl: the chlorine atoms in the molecules serve as the source of ^^""Cl and C1 atoms.…”
Section: Introductionmentioning
confidence: 99%
“…The results from the 34m Cl experiments given in Table 1 were preformed using an electron-beam of an average intensity of about 45 μΑ and an irradiation time of 15 min. When higher currents were reached in our facility, the organic yields for o-C 6 H 4 C1NH 2 were determined as a function of the irradiation time: 12.9% (1 min), 12.2% (2 min), 11.6% (5 min), 10.3% (10min) and 9.4% (20min). Neither an increase of the dose nor an increase of the temperature of the samples during the irradiations have an outspoken effect on the total organic yield.…”
Section: Polymer and Inorganic Yieldsmentioning
confidence: 99%
“…The very high reactivity of aniline in the thermal zone was attributed to fast Η abstraction by thermal 38 CI atoms. BRINKMAN et al reported that 4 mol % aniline added to chlorobenzenes decreased the organic yield from 64% to 31% in case of recoil 3 8 CI atoms, but hardly any effect was found in the case of recoil 34m Cl atoms [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Especially, httle is known about the reactions of recoil atoms, produced by radiative neutron capture, in such systems [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%